Determinants software piracy : attitudes and intentions and Behaviors in Lebanon - Seleim, Ahmed; Khalil, Omar (جامعة الكويت - مجلس النشر العلمي, 2016)
The pervasiveness of the Internet and the progression of information technology have escalated software piracy (SP) worldwide. However, effective measures to curb SP in a particular country cannot be established without knowing the factors that influence SP behaviors in that country. A research model, grounded in the theory of planned behavior (TPB), was used to test three sets of hypotheses relating a number of factors to SP attitude, intention, and behavior among college students in Leba¬non. The results confirm that subjective norms influence attitudes towards SP. Attitude towards SP, perceived behavioral control, and religious commitment influence SP intention, which, in turn, influences SP behavior. Surprisingly, however, the influence of religious commit¬ment on the intention to pirate software is positive. These findings provide partial support for the applicability of TPB in explaining the SP phenomenon in Lebanon, as SP intention is not a strong predictor of SP behavior. Research implications, limitations, and future research are further discussed in the paper.
Keywords: الحاسبات الإلكترونية -- البرمجيات -- القرصنة -- تكنولوجيا المعلومات -- فيروسات الحاسوب -- الأمن المعلوماتى -- الجرائم الإلكترونية -- لبنان